Innovative methodologies between supply and demand: Emergent categories from the Geography and History class - Luna, Diego; Pineda-Alfonso, José Antonio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
At present, educational discourses on innovative methodologies make up an enthusiastic panorama that is not exempt from criticism. The aim of this paper is to understand the real possibilities of success for new methodological proposals in a case study focused on the Geography and History classes of a teacher–researcher. The results obtained allow us to identify a central category of analysis, “methodological ineffectiveness”, and two subcategories, “methodological supply” and “methodological demand”. This confirms the importance of exploring the impact of new methodologies based on the factors and voices specific to each educational context.